Recent Development in Targeting PI3K-Akt-mTOR Signaling for Anticancer Therapeutic Strategies - Khurshid Qazi, Asif; Hussain, Aashiq; Hamid, Abid; Qurishi, Yasrib; Majeed, Rabiya; Ahmad, Mudassier; Ahmad Najar, Rauf; Ahmad Bhat, Javeed; Kumar Singh, Shashank; Afzal Zargar, Mohmmad; Ali, Shakir; Kumar Saxena, Ajit (Anti-Cancer Agents in Medicinal Chemistry, 2013)
Cancer is a diverse class of diseases which differ widely in their cause and biology. The aberrant behavior of cancer reflects up regulation of certain oncogenic signaling pathways that promote proliferation, inhibit apoptosis, and enable the cancer to spread and evoke angiogenesis. Phosphoinositide-3-kinase(PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway controls various biological processes that are important for normal functioning of the cell via cell cycle progression, survival, migration, transcription, translation and metabolism. However, PI3K signaling pathway is dysregulated almost in all cancers which is due to the amplification and genetic mutation of PI3K gene, encoding catalytic and regulatory subunit of PI3K isoforms. The current review focuses on the structural features of various PI3K isoforms including Akt and mTOR and their inhibition using specific small molecule inhibitors in an attempt to achieve an attractive target for cancer prevention and chemotherapy.
Keywords: Anticancer target